INKLUSI PENGENALAN PAJAK ORANG PRIBADI KEPADA SISWA-SISWI SMA KATOLIK SANTO KRITROFORUS 1 - JAKARTA - Hendro Lukman; Kevin Kevin; Sebastian Taniel Mulyadi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Tax is the obligation of every citizen in any country. Taxes which are contributions imposed by the state are treated as state revenues that will be used to organize government and development. Due to the compliance of every citizen who has become a taxpayer, it is important to plan and collect state revenues from taxes. The low level of participation of taxpayers in calculating and reporting tax obligations causes state revenues to not be achieved. The low participation is due to ignorance and non-compliance of taxpayers with obligations. An understanding of taxation, especially individual taxes, is very basic and important in improving tax compliance. Someone will obey if they understand the benefits of taxes paid and the obligations that must be carried out. For this reason, the “Pengabdian Kepada Masyarakat”team provides inclusion of individual tax understanding to St.Kridtoforus 1 Jakarta Catholic High School students. The purpose of providing inclusion of individual tax understanding is to recognize the usefulness of taxes and the taxation system in Indonesia, so that they can instill an obedient and obedient attitude towards fulfilling their tax obligations when they become taxpayers. The inclusion was given in the form of a webinar which was attended by 130 students from class XI and XII both in the Department of Social Sciences and Natural Sciences on October 7, 2021. The results of the evaluation carried out by giving quizzes and evaluation forms, indicated that they could understand the material given. It can be concluded that this inclusion can be digested by the participants. Because high school age or adolescence is an age that will soon become a taxpayer, as well as business opportunities at their age, the inclusion of personal tax understanding can be given to other high school schools.